1986
DOI: 10.1093/jac/18.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Phamacokinetics of aztreonam in the aqueous humour

Abstract: Fifteen patients awaiting cataract extraction were given a 2 g intravenous bolus injection of aztreonam. The mean aztreonam concentrations in the aqueous humour. 1, 2 and 4 h after the injection were 1.22, 1.46 and 2.22 mg/l, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Experimental data from animals (Barza & McCue 1983) suggest that the diffusion from the subconjuctival space to cornea and aqueous humour is satisfactory, while that to vitreous humour is not. In patients, the distribution of aztreonam from plasma to aqueous humour is slow, and low relative concentrations are reached after a single intravenous injection (Haroche et al 1986). Again it is possible that if no active transport out of the aqueous humour occurs, after some time an equilibrium will be reached.…”
Section: Ocular Compartmentmentioning
confidence: 99%
“…Experimental data from animals (Barza & McCue 1983) suggest that the diffusion from the subconjuctival space to cornea and aqueous humour is satisfactory, while that to vitreous humour is not. In patients, the distribution of aztreonam from plasma to aqueous humour is slow, and low relative concentrations are reached after a single intravenous injection (Haroche et al 1986). Again it is possible that if no active transport out of the aqueous humour occurs, after some time an equilibrium will be reached.…”
Section: Ocular Compartmentmentioning
confidence: 99%
“…Studies of aztreonam kinetics in human eye [15] revealed mean aqueous humor levels, 1–4 h after a 2‐g intravenous infusion, of 1.22–2.22 mg/L. These levels far exceeded the MICs for most Enterobacteriaceae, with the exception of Enterobacter spp., but not that of Pseudomonas aeruginosa.…”
Section: Discussionmentioning
confidence: 99%